Kyrgyz Republic : Financial System Stability Assessment including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents key findings of the Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems for the Kyrgyz Republic. Though the Kyrgyz Republic has made progress in addressing macroeconomic imbalances in recent years, its financial system remains small and at a fairly low level of development. Thus, most financial vulnerabilities should be viewed more in terms of their threat to financial sector development than their threat to macroeconomic stability.